Calculation of temperature data from an automatic solar heat supply system - Murat Kunelbayev; Serik Ixanov; Baglan Imanbek; Rashit Omarov; Omar Dauren (Institute of Advanced Engineering and Science, 2023)
This paper calculates the temperature in an automated solar heat supply system. The study used an automatic controller to monitor the temperature data of the entire system. The developed solar heat supply system has a flat solar collector, heat-insulating translucent glass, and double glazing with reduced pressure. The coolant is made of thin-walled corrugated stainless pipe. The heat from the solar flow heats the liquid removed from the collector, and cold water from the siphon enters its place. There is a constant circulation of heat, which increases heat transfer efficiency by eliminating additional partitions between the panel and thermal insulation. The controller has sensors that register using field-programmable gate array (FPGA) STM32, designed to monitor the entire solar system, and the actuators include power relays. During the experiment, it was found that temperature sensors save energy by 2% due to the use of power relays, which has a significant impact on the service life of the equipment.